2022
DOI: 10.1177/10732748221143389
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Outcomes of Surgery Versus Endoscopic Treatment in Patients With Siewert Type II T1M0N0 Adenocarcinoma of the Esophagogastric Junction

Abstract: Objective We compared the long-term prognosis of surgery and endoscopic treatment (ET) in patients diagnosed with Siewert Type II pT1N0M0 adenocarcinoma of the esophagogastric junction (AEG). Methods Using the Surveillance, Epidemiology, and End Results (SEER) database, we performed a real-world retrospective cohort study and enrolled patients with Siewert Type II pT1N0M0 AEG who underwent surgery or endoscopic treatment (ET) from 2010 to 2018. Matched cohorts were generated using propensity score matching Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Chen et al ( 38 ) found that the procedure speed of ESD for early AEG is slower than that for early gastric carcinoma, possibly due to AEG extending beyond the cardia, including the angle of His. However, endoscopic treatment (including ESD) remains an effective alternative to surgery for the treatment of early AEG based on comparable long-term outcomes ( 18 , 20 ). With the advancements in endoscopic treatment, early AEG can be effectively resected by EMR/ESD with fewer complications, better preservation of gastric function, a shorter duration of hospital stay, and a lower cost compared with traditional gastrectomy or esophagectomy ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al ( 38 ) found that the procedure speed of ESD for early AEG is slower than that for early gastric carcinoma, possibly due to AEG extending beyond the cardia, including the angle of His. However, endoscopic treatment (including ESD) remains an effective alternative to surgery for the treatment of early AEG based on comparable long-term outcomes ( 18 , 20 ). With the advancements in endoscopic treatment, early AEG can be effectively resected by EMR/ESD with fewer complications, better preservation of gastric function, a shorter duration of hospital stay, and a lower cost compared with traditional gastrectomy or esophagectomy ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (38) found that the procedure speed of ESD for early AEG is slower than that for early gastric carcinoma, possibly due to AEG extending beyond the cardia, including the angle of His. However, endoscopic treatment (including ESD) remains an effective alternative to surgery for the treatment of early AEG based on comparable longterm outcomes (18,20). With the advancements in endoscopic For the differentiation variable, well-differentiated is defined as 1, moderately differentiated is defined as 2, and poorly differentiated or undifferentiated is defined as 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, there are several comparative studies of the results of endoscopic resections and those of MIS. Chen et al [ 13 ], performed a propensity study to evaluate the survival of patients treated by the two types of approaches and found that no significant difference was observed in the 5-year cumulative incidence of cancer-specific death between the cohorts and that the type of treatment was not a prognostic factor [hazard ratio (HR) = 1.51, 95% confidence interval (95%CI): 0.81-2.81, P = 0.20) in multivariate Cox analysis. Similar results were reported by other authors: Overall survival (OS) rates at 5 years were not statistically significantly different (93.9% vs 97.3%)[ 14 ], in another study (93.3 vs 92.9%; P = 0.282)[ 15 ], concluding that endoscopic submucosal dissection (ESD) may be an effective alternative to surgery, for the treatment of early GOJ cancer.…”
Section: Indications and Types Of Mis For Goj Adenocarcinomamentioning
confidence: 99%